Arachidonic Acid 15-Lipoxygenase: Effects of Its Expression, Metabolites, and Genetic and Epigenetic Variations on Airway Inflammation - Xu, Xu; Li, Jingyun; Zhang, Yuan; Zhang, Luo (Allergy, asthma & immunology research, 2021)
Arachidonic acid 15-lipoxygenase (ALOX15) is an enzyme that can oxidize polyunsaturated fatty acids. ALOX15 is strongly expressed in airway epithelial cells, where it catalyzes the conversion of arachidonic acid to 15-hydroxyeicosatetraenoic acid (15-HETE) involved in various airway inflammatory diseases. Interleukin (IL)-4 and IL-13 induce ALOX15 expression by activating Jak2 and Tyk2 kinases as well as signal transducers and activators of transcription (STATs) 1/3/5/6. ALOX15 up-regulation and subsequent association with phosphatidylethanolamine-binding protein 1 (PEBP1) activate the mitogen-activated extracellular signal-regulated kinase (MEK)-extracellular signal-regulated kinase (ERK) pathway, thus inducing eosinophil-mediated airway inflammation. In addition, ALOX15 plays a significant role in promoting the migration of immune cells, such as immature dendritic cells, activated T cells, and mast cells, and airway remodeling, including goblet cell differentiation. Genome-wide association studies have revealed multiple ALOX15 variants and their significant correlation with the risk of developing airway diseases. The epigenetic modifications of the ALOX15 gene, such as DNA methylation and histone modifications, have been shown to closely relate with airway inflammation. This review summarizes the role of ALOX15 in different phenotypes of asthma, chronic obstructive pulmonary disease, chronic rhinosinusitis, aspirin-exacerbated respiratory disease, and nasal polyps, suggesting new treatment strategies for these airway inflammatory diseases with complex etiology and poor treatment response.